INFORMED CONSENT IN GENETIC REASEARCH - Chakar, Ljupco; Stankov, Aleksandar; Pavlovski, Goran; Bitoljanu, Natasha; Belakaposka Srpanova, Viktorija; Ivcheva, Ana; Siamkouri, Rosica; Jakjovski, Zlatko (Journal of Morphological Sciences, 2023)
Recognizing the ethical, legal, and social implications (ELSI) of genetic testing becomes crucial for physicians in the face of complex medical issues, as they are increasingly expected to counsel their patients regarding the medical, psychological, and social responses arising from genetic information. Genetic medicine, with its extreme complexity and the potential repercussions on an individual's life, raises important questions in the ethical, deontological, and legal realms of medicine, playing a primary role in personalized medicine. The aim of this paper is to underscore the significance of informed consent and to provide insights into the ethical procedures associated with genetic testing. Keywords: informed consent, genetic, genomic testing, ELSI